Intrahepatic Cholestasis due to Cytomegalovirus Infection and Extrahepatic Cholestasis due to Sludge Bile with Confirmed COVID-19 - Yusri Dianne Jurnalis; Erli Meichory Viorika (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Human Cytomegalovirus (CMV) is a Beta-Herpes virus that leads to congenital infection in 0.4% to 2,3 % of all newborns. Diagnosis of CMV infection includes the culture of the nasopharynx, saliva, and urine. Serologic tests are also beneficial for CMV diagnosis. IgM CMV-specific antibodies can be monitored. Biliary sludge is a mixture of particulate solids that have precipitated from bile. Laparoscopic cholecystectomy offers the most definitive therapy for biliary sludge. Case presentation: A 2-month-old boy complained yellow appearance since the age of 1 week ago. Looks pale. Defecation was sometimes colored putty since the age of 2 weeks. Blood laboratory examination with hemoglobin 8,7 gr/dL, Prothrombin time, activated partial thromboplastin time, and liver function were increased. Bilirubin, alkaline phosphatase, and Gamma GT were increased. Two-phase and abdominal USG were biliary atresia. PCR CMV examination with urine and blood sample was positive. Head USG was consistent with CMV infection. Cholangiography showed sludge bile with liver cirrhosis. Therapy gansiklovir IV for 14 days then gansiklovir per oral for 6 months. Conclusion: Cholangiography is the definitive diagnosis for biliary sludge. CMV is a congenital infection that causes asymptomatic to multiple severe symptoms, so it is necessary to monitor children for adherence to treatment, improve nutritional status and reduce morbidity and mortality rates.